2022
DOI: 10.1002/jgh3.12817
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of sleep quality in inactive inflammatory bowel disease

Abstract: Poor sleep in people with inflammatory bowel disease (IBD) has been demonstrated to be prevalent and has been associated with disease activity. This meta‐analysis aimed to assess the prevalence of poor sleep in inactive IBD and in controls by considering cohort and cross‐sectional studies. Electronic databases were searched for publications from inception to 1 November 2021. Poor sleep and IBD activity were defined according to self‐reported subjective sleep measures. A random effects model was used to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
1
10
0
1
Order By: Relevance
“…IBD may impair sleep through its myriad of disabling symptoms, including abdominal pain and nocturnal diarrhea 11 . Poor sleep is more common in those with IBD than controls, 11 more common in those with active IBD than inactive IBD, 11,12 and remains more common in those with inactive IBD than controls 13 . Endoscopically or histologically active IBD in the absence of any IBD symptoms may be sufficient to disrupt sleep 14,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IBD may impair sleep through its myriad of disabling symptoms, including abdominal pain and nocturnal diarrhea 11 . Poor sleep is more common in those with IBD than controls, 11 more common in those with active IBD than inactive IBD, 11,12 and remains more common in those with inactive IBD than controls 13 . Endoscopically or histologically active IBD in the absence of any IBD symptoms may be sufficient to disrupt sleep 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Poor sleep is more common in those with IBD than controls, 11 more common in those with active IBD than inactive IBD, 11,12 and remains more common in those with inactive IBD than controls. 13 Endoscopically or histologically active IBD in the absence of any IBD symptoms may be sufficient to disrupt sleep. 14,15 There have been several association studies of sleep and IBD with comorbid depression [16][17][18][19][20][21][22][23] frequently associated with poor sleep, and low physical activity associated with poor sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Poor sleep quality is highly prevalent in active IBD patients, ranging from 73 to 100% ( 4 ), much higher than in healthy controls. Inactive IBD patients were also found to have poorer sleep quality than healthy controls, suggesting that sleep quality in IBD patients is not only due to IBD-related symptoms ( 5 ). Therefore, it needs to describe the associations between sleep quality and IBD to inform the development of therapies that enhance the quality of life among IBD patients.…”
Section: Introductionmentioning
confidence: 99%
“…It also found that poor sleep quality is one of the main concerns for patients with chronic intestinal disease, which can negatively impact health and work productivity in the long term ( 6 ). As an immune-related gastrointestinal disease, the sleep quality in IBD can affect not only its symptoms but also might act as an extraintestinal manifestation and aggravating or etiological factor ( 5 ). However, although poor sleep quality is a significant health concern among IBD patients, it is often underappreciated in clinical medicine.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Poor sleep is more common in those with IBD than controls, 3 more common in those with active IBD than inactive IBD, 3 , 4 and more common in those with inactive IBD than controls. 5 Mental health conditions such as anxiety and depression have been associated with poor sleep in an IBD population. 6–13 …”
Section: Introductionmentioning
confidence: 99%